Modernização dos sistemas de registro de imóveis e a busca por interconexão e interoperabilidade no contexto brasileiro: lições da União Europeia - Borba, Nicolas Frietto de (Universidade do Vale do Rio dos Sinos, 2024)
This master’s thesis examines the modernization of land registration with a focus on lessons learned from the European Union (EU), drawing on the models of some country members. It identifies how the Brazilian system operates and the challenges faced in Brazil, such as the lack of interconnection and training. This study adopts a predominantly bibliographic methodology with a qualitative approach. The first chapter analyzes the Brazilian context, evaluating the steps taken towards modernizing property records and identifying current challenges. The second chapter explores the EU's experiences in modernizing land registry, highlighting practical recommendations and strategies. The third chapter summarizes the main conclusions, emphasizing the relevance of modernizing land registry for Brazil and pointing towards future research directions. Inspired by the EU's experiences, the research proposes adaptable strategies to accelerate the modernization of Brazilian land registry, emphasizing interconnection and interoperability of systems, as well as information and communication technology. The research demonstrates that continuous modernization is essential to ensure legal security and promote economic and social development in the country. Through the guidelines outlined in this study, the Brazilian land registry system can evolve towards a more unified, efficient, and transparent system.
Keywords: Registro de imóveis; Tecnologias de Informação e comunicação; União Europeia (UE); Brasil; Land registration; Information and Communication Technologies (ICTs); European Union (EU); Brazil; ACCNPQ::Ciências Sociais Aplicadas::Direito